Timber engineering research and education in Malaysia - Jumaat, Mohd Zamin; Rahim, Ahmad Hazim Abdul; Othman, Johari; Razali, Fadini Mohamad (2006)
The current state of affairs in Malaysia is that the interest in using timber as a structural member is almost non-existence. Use of structural timber currently is limited to formworks and trusses. Even in this usage it is competing fiercely with steel and other materials. Knowledge on timber properties and design are also lacking among the architects and engineers. In terms of timber researches, a number of research works are currently being conducted while in education only a few universities are offering courses on timber design. As works that needed to be done, the main emphasize should be in terms of promotions. These include conducting short courses, seminars and producing relevant timber design materials to the engineers and architect, in particular, and the public in general. Works to lobby the appropriate authorities to include timber design in engineering course in universities and to change by laws that restrict the use of timber as construction materials should also be emphasized.